Hubungan Karakteristik Keluarga dan Tingkat Ketahanan Pangan Rumah Tangga dengan Kejadian Stunting pada Balita (Studi di Wilayah Kerja Puskesmas Singgahan, Kabupaten Tuban) - Syarifah, Nur Laila; Sumarmi, Sri (Media Gizi Kesmas, 2024)
Background: Stunting is chronic malnutrition that occurs in a long time and there are symptoms such as shorter stature compared to their age. Stunting can be caused by several factors, both directly and indirectly. The direct factors are nutritional deficiency and infection, while the indirect factors are household food security and family characteristics. Objectives: The objective of this study is to examine the correlation between family characteristics and the degree of household food security with the occurrence of stunting in toddlers residing in the Singgahan Health Center's jurisdiction in Tuban Regency. Method: The chosen research methodology employs a quantitative analytical approach and adopts a cross-sectional design. The study's sample consists of 95 individuals, selected using a multistage random selection process. The collection of research data involved the utilization of many methods, including height measurements, interviews, and the administration of the Household Food Insecurity Access Scale (HFIAS) questionnaire. Additionally, the data obtained in the study were subjected to analysis using the Chi-Square test. Results: The results showed that the prevalence of stunting was relatively high, namely 41.1%. Not only that, the prevalence of families categorized as severe food insecure was also found, which was 13.7%. Based on the results of the study, a relationship was found between the father's occupation and the incidence of stunting in toddlers (p=0.007), family income and the incidence of stunting in toddlers (p=0.013), food expenditure and the incidence of stunting in toddlers (p=0.019), and the level of food security. household food with the incidence of stunting in toddlers (p=0.033). Conclusion: The occurrence of stunting in young children can be attributed to familial traits and the degree of food security within the home. Insufficient household income has a detrimental impact on the ability of individuals to obtain enough access to food. Respondents are anticipated to enhance the quality of balanced nutrition in toddlers in accordance with the guidelines provided by the Ministry of Health of the Republic of Indonesia. Enhancing household food security can be achieved through the provision of training and the development of productive business skills, hence augmenting income and facilitating improved food accessibility.